Modeling of the Kinetic Experiment of Dicyclopentadiene Olygomerization; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Lyapkov A. A. Aleksey Alekseevich; Bondaletov V. G. Vladimir Grigoryevich; Melnik E. I. Elena Ivanovna; Borisov G. V. Georgy Vitalievich (Chemistry and Physics of Materials Surface, 2014)
Title screen